UNSUR SIMBOLIS DAN ESTETIS DALAM SENI PAHAT SUKU DAYAK BENUAQ DAN TUJUNG DI KALIMANTAN TIMUR - Hartatik Hartatik (Balai Arkeologi Kalimantan Selatan, 2008)
The Benuaq and Tunjung inhabit the high hinterland of Kutai Barat in the Province of East Kalimantan. Both communities have the sustainable potency to uphold their skill in wood carving; the existence of balontang, tugu ngugu tautn, templaq, klerekng and ornaments on old lamin, which abundantly found in their village signify their centuries-old competence in wood carving. Nevertheless, there are some style and type differences on carved wooden object between the Benuaq-Tunjung and that of the Ngaju, Lawangan and Maanyan. For instance, physically, the Ngaju, Lawangan and Maanyan tends to carve plain and massive wooden figures, whereas those of the Benuaq-Tunjung are more dynamic and enriched with attractive scrolls. This article discusses the aesthetic and symbolic representation of balontang, tugu ngugu tautn, templaq, klerekng, ornaments on old lamin.